Analisis Penerapan Hukum Pidana dan Implikasi Sosial terhadap Tindak Kekerasan dalam Konflik Lingkungan Pesisir akibat Pengerukan Laut - Michel Priscila; Talitha Maheswari Ning Atmojo; Sekar Galuh Adrelia; Akmalia Salsabila; Muhamad Noval Faris Pratama; Mochamad Yulian Fadhli Saputra; Cikal Aldrich Adilhum; Zidan Nugraha; Luthy Yustika (PT. Saha Kreasi Indonesia, 2026)
Coastal environmental conflicts caused by sea dredging often lead to tensions between fishing communities and parties exploiting natural resources. These tensions frequently escalate into protest actions accompanied by acts of violence. This study aims to analyze the application of criminal law to violent acts during fishermen’s protests and to examine the social implications of handling such cases. The research method employed is a normative juridical approach with qualitative analysis of legislation, legal doctrines, and relevant cases. The findings indicate that the application of criminal law often emphasizes repressive measures without addressing the root causes of environmental conflict, resulting in social impacts such as the marginalization of fishermen and distrust toward law enforcement authorities. A more comprehensive approach is required, integrating the protection of coastal communities’ rights with restorative measures.